2021
DOI: 10.1002/jimd.12415
|View full text |Cite
|
Sign up to set email alerts
|

Role of liver transplantation in urea cycle disorders: Report from a nationwide study in Japan

Abstract: Urea cycle disorders (UCDs) are inherited metabolic diseases causing hyperammonemia by defects in urea cycle enzymes or transporters. Liver transplantation (LT) currently is the only curative treatment option until novel therapies become available. We performed a nationwide questionnaire-based study between January 2000 and March 2018 to investigate the effect of LT in patients with UCDs in Japan. A total of 231 patients with UCDs were enrolled in this study. Of them, a total of 78 patients with UCDs (30 male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
1
22
0
1
Order By: Relevance
“…Despite the treatment opportunities, mortality rates are still high in neonatal-onset UCDs-around 60%. In our series of patients mortality rate was similar to the rate reported in the literature (%50 among neonatal cases) (8,10). A meta-analysis that has reviewed the observational studies on UCDs, that were published over more than 35 years, has concluded that all UCDs, except female OTCs, have high risks for early onset disease, and neonatal death except for ASLD.…”
Section: Table I: Clinical Characteristics Of Patients Involvedsupporting
confidence: 86%
“…Despite the treatment opportunities, mortality rates are still high in neonatal-onset UCDs-around 60%. In our series of patients mortality rate was similar to the rate reported in the literature (%50 among neonatal cases) (8,10). A meta-analysis that has reviewed the observational studies on UCDs, that were published over more than 35 years, has concluded that all UCDs, except female OTCs, have high risks for early onset disease, and neonatal death except for ASLD.…”
Section: Table I: Clinical Characteristics Of Patients Involvedsupporting
confidence: 86%
“…Previously, we had conducted nation-wide surveys on Japanese patients with urea cycle disorders (UCDs), such as OTCD, carbamoyl phosphate synthetase 1 deficiency, N-acetylglutamate synthase deficiency, argininosuccinate synthetase deficiency, argininosuccinate lyase deficiency, and arginase 1 deficiency ( Kido et al, 2021c ; 2021a ; 2021b ; 2021d ). In the current survey, we acquired the clinical data of 128 patients with OTCD (73 males and 55 females), including genetic information of 62 of them (57 families).…”
Section: Methodsmentioning
confidence: 99%
“…The OTCD phenotype is extremely heterogeneous. For instance, many male OTCD patients have severe hyperammonemic crisis in the neonatal stage, whereas others develop late-onset manifestations, including hyperammonemic coma ( Kido et al, 2012 ; Kido et al, 2021a ; Kido et al, 2021b ). On the contrary, females with heterozygous pathogenic variants in the OTC gene may develop a variety of clinical manifestations, ranging from an asymptomatic condition to severe hyperammonemic attack, owing to the skewed lyonization phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique is not as convenient as routine liver function tests [16]. The peak blood ammonia level of >356 μmol/L predicted poor neurodevelopmental outcomes in the patients undergoing LTx [17].…”
Section: Post-transplant Managementmentioning
confidence: 99%
“…However, it did not improve neurodevelopmental outcomes in the patients with severe symptomatics, because hyperammonemia exerts early brain damage. Urgent LTx in another UCD, i.e., arginine succinate synthase deficiency, may improve the longitudinal cognitive and behavioural outcomes [17].…”
Section: Clinical Effectmentioning
confidence: 99%